PENGUKURAN SURVEY KEPUASAN PEGAWAI PDAM TIRTA MERAPI KABUPATEN KLATEN - S, Anna Febrianty; Nugroho, Arif Julianto Sri; Almasitoh, Ummu Hany; Uningowati, Dwi Wahyuni; Pratomo, Sigit Adhi; Tasari, Tasari (Universitas Of Surakarta, 2024)
This research aims to determine the influence of work environment, supervision, carrer development, compensation and allowance on employee satisfaction PDAM Tirta Merapi Klaten.The type of this research is Quantitative research with regression analysis. The population in this study as all employees of PDAM Tirta Merapi Kabupaten Klaten amount to 155 people. The multiple regression results show Y = 7.001 + 0.342 X1 + 0.689 X2 + 0.246 X3 + 0.338 X4 with significance p values 0.019, 0.01 0.02 dan 0.001. Regression coefficients of independent variables which are positive means that independent variables has a direct effect on employee job satisfaction and vice versa. It means that the hypothesis proposed in this research as proven to be true, that is, it is assumed that supervision in career has a significant and dominant effect on employee satisfaction in PDAM Tirta Merapai Kabupaten Klaten